2015
DOI: 10.1016/j.jmb.2014.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically Disordered C-Terminal Tails of E. coli Single-Stranded DNA Binding Protein Regulate Cooperative Binding to Single-Stranded DNA

Abstract: The homotetrameric E. coli single stranded DNA binding (SSB) protein plays a central role in DNA replication, repair and recombination. E. coli SSB can bind to long single-stranded (ss) DNA in multiple binding modes using all four subunits ((SSB)65 mode) or only two subunits ((SSB)35 binding mode), with the binding mode preference regulated by salt concentration and SSB binding density. These binding modes display very different ssDNA binding properties with the (SSB)35 mode displaying highly cooperative bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
157
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(173 citation statements)
references
References 57 publications
10
157
3
Order By: Relevance
“…C-terminal disordered tails of E.coli single stranded DNA binding proteins belong to region R1 and these tails engender positive cooperativity in single stranded DNA binding. Cooperativity in single stranded DNA binding is abolished if the tails are eliminated or replaced with sequences drawn from the R3 region [63]. …”
Section: Connecting Ccrs To Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…C-terminal disordered tails of E.coli single stranded DNA binding proteins belong to region R1 and these tails engender positive cooperativity in single stranded DNA binding. Cooperativity in single stranded DNA binding is abolished if the tails are eliminated or replaced with sequences drawn from the R3 region [63]. …”
Section: Connecting Ccrs To Functionmentioning
confidence: 99%
“…This should be helpful for establishing the connections between changes to SCRs and functions / phenotypes controlled by polyampholytic sequences drawn from regions R2 and R3. A range of targets for such design efforts is readily available from the rich literature on IDPs with established functional roles for polyampholytic sequences [8,9,14,19,63,7477]. Of course, the patterning of oppositely charged residues quantified by κ is not the only way to conceive of modulating SCRs.…”
Section: Enabling De Novo Sequence Designmentioning
confidence: 99%
“…These differences are possibly due to intrinsic differences in binding activity, as well as a decrease in cooperative binding due to the truncation of nine amino acids from the C-termini of B. anthracis and S. aureus SSBAs. 26 The binding activities of all four SSBAs were considered qualified for EMSA and HTS assays. Glanzer et al…”
Section: Resultsmentioning
confidence: 99%
“…In the proposed model the Ct tail is bound to the OB fold in the absence of ssDNA, while in the presence of ssDNA the Ct tail is released, thus leaving it free for the interactions with other cellular proteins. Recently it was demonstrated that an intrinsically disordered C-terminal region of E. coli SSB protein participated in cooperative binding to ssDNA (16). All these results suggest an important regulatory role of Ct domain.…”
Section: The Ct Domain Terminates With a Conserved Acidic Hexapeptimentioning
confidence: 98%
“…Recently, it was shown that shortening of C-terminal region of E. coli SSB protein had an impact on cooperative binding to ssDNA (16). It was also reported that extension of Ct domain slowed cell growth rate, indicating impaired protein function in vivo (14).…”
Section: Amino Acid Composition Analysis Of Bacterial Ssbsmentioning
confidence: 99%